PENGARUH DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. LEO UTAMA MOTOR BATAM - Laely Ma’rufah; Tibrani Tibrani; Ramon Zamora (University of Riau Kepulauan, 2015)
The research was conducted PT Leo Utama Motor Batam.The purpose of this study to determine the effect of work discipline and satisfied to the performance of employees either separately (partial) or jointly (simultaneously). In this study,the outhors use a sample of 55 employees is taken as a whole from the total population (employees).while this type of data is primary data and secondary data. The primery data source obtained from the questionnaires with employees who are competent in the PT Leo Utama Motor Batam.While the sources of secondary data obtained from PT Leo Utama Motor Batam.Documents obtained from the literature are related and can support as well as useful for this study. Data gathering technique conducted by way of interviews and questions data analysis was performed with descriptive setatistics, which are used to describe the given picture of the object studied througth a sample or population data obtained in the field associated with the relevant theories and techniques of the quantitative analysis of the data that has been given a score according to the scale of measurement used the likert scale and to test the results using SPSS (Statistical Product and Service Solution) version 20. From the results of the study outhors conclude that the partial Discipline (X1) Has positif and significant impact on performance employees (Y) and satisfied (X2) has positif and significant impact on performance employees (Y) and simultaneously work Discipline and Satisfied have a positif and significant (Strong) against employees (Y)